Endothelial CD40 mediates microvascular von Willebrand factor-dependent platelet adhesion inducing inflammatory venothrombosis in ADAMTS13 knockout mice - Tahir, Sibgha; Wagner, Andreas H.; Dietzel, Steffen; Mannell, Hanna; Pircher, Joachim; Weckbach, Ludwig T.; Hecker, Markus; Pohl, Ulrich (Thrombosis and haemostasis, 2020)
Background von Willebrand factor (vWF) plays an important role in platelet activation. CD40-CD40 ligand (CD40L) induced vWF release has been described in large vessels and cultured endothelium, but its role in the microcirculation is not known. Here, we studied whether CD40 is expressed in murine microvessels in vivo, whether CD40L induces platelet adhesion and leukocyte activation, and how deficiency of the vWF cleaving enzyme ADAMTS13 affects these processes. Methods and Results The role of CD40L in the formation of beaded platelet strings reflecting their adhesion to ultralarge vWF fibers (ULVWF) was analyzed in the murine cremaster microcirculation in vivo. Expression of CD40 and vWF was studied by immunohistochemistry in isolated and fixed cremasters. Microvascular CD40 was only expressed under inflammatory conditions and exclusively in venous endothelium. We demonstrate that CD40L treatment augmented the number of platelet strings, reflecting ULVWF multimer formation exclusively in venules and small veins. In ADAMTS13 knockout mice, the number of platelet strings further increased to a significant extent. As a consequence extensive thrombus formation was induced in venules of ADAMTS13 knockout mice. In addition, circulating leukocytes showed primary and rapid adherence to these platelet strings followed by preferential extravasation in these areas. Conclusion CD40L is an important stimulus of microvascular endothelial ULVWF release, subsequent platelet string formation and leukocyte extravasation but only in venous vessels under inflammatory conditions. Here, the lack of ADAMTS13 leads to severe thrombus formation. The results identify CD40 expression and ADAMTS13 activity as important targets to prevent microvascular inflammatory thrombosis.
Gesehen am 20.04.2020